Videoendoscopic Inguinofemoral Lymphadenectomy for Vulvar Cancer. Literature Review - K. V. Menshikov; B. F. Kiyamov; Т. К. Girfanov (Креативная хирургия и онкология)
Vulvar cancer is one of the rare malignant neoplasms treated in gynecologic oncology. This type of cancer ranks nineteenth among the most common types of malignant neoplasms in European women. The main method for treating localized vulvar cancer is surgery. Starting from the stage TIb and with the lateral location of the tumor, surgical treatment is indicated (vulvectomy and inguinofemoral lymphadenectomy). The classical Ducuing surgical procedure, which was developed in 1934, is accompanied, in most cases, by such postoperative complications as lymphorrhea, delayed healing of surgical wounds, and suppurative septic complications. One way to minimize them is to use videoendoscopic technologies. The provided review of studies on the subject presents the results of using videoendoscopic technologies (e.g., a significant reduction in the number of postoperative complications). Noteworthy is that the operative time decreases with experience in performing such interventions. Randomized studies are needed to evaluate the long-term results when using videoendoscopic technologies to perform an inguinofemoral lymphadenectomy.